Laparoscopic vs. Open Pyloromyotomy in Treatment of Infantile Hypertrophic Pyloric Stenosis - Ismail, Ibrahim; Elsherbini, Radi; Elsaied, Adham; Aly, Kamal; Sheir, Hesham (Frontiers in Pediatrics, 2020)
Background/ Purpose: Laparoscopic pyloromyotomy gained wide popularity in management of pyloric stenosis with contradictory results regarding its benefits over classic open approach. This study aimed at comparing both regarding their safety, efficiency and outcome. Methods: This is a prospective randomized controlled study performed from April 2017 to April 2019. It included 80 patients, divided randomly into 2 groups; where laparoscopic pyloromyotomy performed in group A and open pyloromyotomy in group B. Both groups were compared regarding operative time, postoperative pain score, time required to reach full feeding, hospital stay, complications and parents' satisfaction. Results: Median operative time was 21 minutes in group A versus 30 minutes in group B (P=0). PAIN scores were generally higher in group B with more doses of analgesics required (P=0). Mean time needed to reach full feeding was 15.2 and 18.8 hours in groups A and B respectively (P=0). Median hospital stay was 19 hours in group A and 22 hours in group B (P=0.004). Parents' satisfaction also was in favor of group A (P= 0.045). Although no significant difference was reported between both groups regarding early and late complications, some complications as mucosal perforation and incomplete pyloromyotomy occurred in the laparoscopic group only. Conclusion: Laparoscopic pyloromyotomy was found superior to open approach regarding faster operative time, less need of analgesics, easier development of oral feeding, shorter hospital stay and better parents' satisfaction. Yet, there still some concerns about the safety and efficiency of this procedure over open technique.